Media Image of the Arctic: Towards Qualified Human Resources - Inga M. Zashikhina (Арктика и Север)
The article is devoted to the relevant topic — the Russian Arctic labor resources. The potential labor force of the Arctic today includes representatives of generation Z, graduates of Russian universities. The strategic issue of attracting labor resources to the Arctic has a target audience of young people. The governmental policy agent is mass media. The media provide public narratives of social constructs. The media are used to represent such an important social construct for the state as the Russian Arctic. The established media image of the Arctic includes characteristics related to the harsh weather conditions, the region’s resource endowment, its military potential, and environmental problems. The traditional components of the media image of the Arctic have little significance in terms of highlighting the region’s human resource potential. The existing media image of the Arctic is uninformative for potential Arctic labor force due to the features of public information consumption and processing by young people. The content of the media image has a specific pragmatic component that is directly related to the issue of labor vacancies, living conditions, work and lifestyle in the location of the vacancy. The aim of the study is to determine the media image of the Arctic corresponding to the Russian government’s strategy for the development of the area. As a result, recommendations are made to adjust the media image of the Arctic to solve the problem of staffing the Arctic. The scientific novelty of the study is in the data obtained through surveys of Arctic university students. This data allows us to assess the degree of young people’s awareness of the possibilities for applying professional competencies in the development of the Arctic. The study of the modern youth features, including the character of media consumption, also constitutes scientific novelty in the study of tools for the formation of Arctic workforce. Practical significance is represented by the possibilities that will provide a new media image of the Arctic for the creation of human resources potential of the AZRF.